Risk factors in acute respiratory distress syndrome among children with cancer in Brazilian Amazon: An observational study (Research, Society and Development, 2021)
This study was undertaken to determine the incidence and potential risk factors associated with Acute Respiratory Distress Syndrome (ARDS) in pediatric oncologic patients undergoing invasive mechanical ventilation and the association between mortality risk factors and ARDS. Retrospective cohort study was conducted using data analysis of patients on admission to the PICU, that were submitted to invasive mechanical ventilation for over 24 hours. Shapiro-Wilk test and bivariate analysis within the group exposed to ARDS and the one not exposed, as well as Fisher's, Wilks G, chi-square tests, and Poisson logistic regression were applied, with significant variables p